2021
DOI: 10.1002/prep.202100010
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3D Porous Network Nanostructure of Nitrated Bacterial Cellulose Gel with Eminent Heat‐Release, Thermal Decomposition Behaviour and Mechanism

Abstract: In this study, a novel three‐dimensional (3D) porous cross‐link network structure of nitrated bacterial cellulose (NBC) nano‐gel, as an energetic gel matrix for fabrication of nanocomposite energetic materials, (nEMs) was synthesized by sol‐gel synthetic and the freeze‐drying technology. The analysis results revealed that the unique network structure with abundant of nano‐porous, which made the thermal behaviour of the NBC gel different from that of raw NBC. The thermal decomposition kinetic and mechanism of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
3
9
0
Order By: Relevance
“…The synthesis of CNs requires that cellulose-concomitant components be removed from plant raw materials, and these processes inflict environmental damage [21]. Research has focused on finding new energetic materials [22][23][24] with a high purity and a unique reticulate nanostructure [25,26] concerning nanocellulose [27][28][29] and, most notably, bacterial cellulose (BC) as the leader among the nanocelluloses [30][31][32], has presently reached its highest demand [33][34][35][36][37]. The broad application prospects and benefits of nanocellulose nitrate-based energetic materials were overviewed back in 2014 [38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of CNs requires that cellulose-concomitant components be removed from plant raw materials, and these processes inflict environmental damage [21]. Research has focused on finding new energetic materials [22][23][24] with a high purity and a unique reticulate nanostructure [25,26] concerning nanocellulose [27][28][29] and, most notably, bacterial cellulose (BC) as the leader among the nanocelluloses [30][31][32], has presently reached its highest demand [33][34][35][36][37]. The broad application prospects and benefits of nanocellulose nitrate-based energetic materials were overviewed back in 2014 [38].…”
Section: Introductionmentioning
confidence: 99%
“…The initial works on the synthesis of CN from BC (CN BC) were described as early as 2006 [22] and 2010 [23]. The next wave of larger and more extensive studies on CN BC started in 2018 [24] and continues to the present [25][26][27][28][29][30][31][32][33][34][35][36][37] because CN BC has several advantages over plant-based cellulose nitrates, in particular, its high stability due to the ultrafine, high-purity, reticulate fibrous structure.…”
Section: Introductionmentioning
confidence: 99%
“…4 Nevertheless, NC is derived from various plant fibers, which leads to the presence of some impurities, such as lignin, hemicellulose, pectin, starch, and other plant materials. 5 Moreover, it is wellknown that there is a contradiction between the mechanical properties and energy performance of NC. 6 Studies have shown that NC with a higher nitrogen content has higher energy but lower mechanical strength, especially its brittleness feature in low-temperature conditions, which limits the development of high-energy and high-strength propellants.…”
Section: Introductionmentioning
confidence: 99%
“…In the domain of energetic materials (EMs), energetic binders play a vital role in supporting the energy and mechanical performances of propulsion, such as solid rocket propellants and gun propellants. Therein, nitrocellulose (NC) is regarded as one of the most significant industrial materials because of its unique physical properties and is widely used in plastics, paints, lacquers, propellants, explosives, and so forth . Nevertheless, NC is derived from various plant fibers, which leads to the presence of some impurities, such as lignin, hemicellulose, pectin, starch, and other plant materials . Moreover, it is well-known that there is a contradiction between the mechanical properties and energy performance of NC .…”
Section: Introductionmentioning
confidence: 99%
“…In previous works on EMs, scientists have devoted numerous research efforts into investigating the coating additives, for instance, wax, graphite, polymers, , or other insensitive explosives . Typically, polymer materials have always been chosen as binders used in explosive formulations for a long time to enhance the mechanical performances of explosive charges and desensitize the high explosives, which are named plastic-bonded explosives (PBXs). Therefore, coating DMs on the surface of explosives has been proven to be a useful and effective method to desensitize EMs.…”
Section: Introductionmentioning
confidence: 99%